ChemInform Abstract: Catalytic Regioselective Oxidation of Glycosides. Issue 49 (3rd December 2013) - Jaeger, Manuel; Hartmann, Marcel; de Vries, Johannes G.; Minnaard, Adriaan J.
Abstract This is the first catalytic, regioselective oxidation of unprotected pyranosyl glycosides.